Sosialisasi Penerapan Pembelajaran Berbasis Modul Ajar Merdeka Belajar di MIN 1 Langkat - Diani Syahfitri; Emha Fidiyan Akhadi; Rizka Rizka (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
This community service aims to enhance elementary school teachers' competencies in developing and implementing teaching modules based on the Merdeka Belajar Curriculum. The participatory approach included focus group discussions, training and workshops, on-site mentoring, and joint evaluation and reflection. The results indicate significant improvements in teachers' ability to implement teaching modules, use educational technology, and actively participate in discussion forums and working groups. The expected social transformation, including behavioral changes and the emergence of local leaders, was achieved through this approach. These results support constructivism and project-based learning theories, demonstrating that a collaborative and sustainable approach is effective in teachers' professional development.